ASSESSMENT OF THE QUALITY AND IRRIGATION PURPOSE SUITABILITY OF ALLUVIAL WATER IN ERFOUD, MOROCCO - Latos, Beata; Szczucińska, Anna; Kozłowski, Rafał (Quaestiones Geographicae, 2019)
Dry areas are especially exposed to the risk of water shortages and elevated mineralization. High water salinity, caused by low precipitation, high evaporation and human impact, usually strongly limits the use of the water for irrigation. The aim of the study was to assess the quality and irrigation purpose suitability of alluvial water in the Erfoud oasis, Morocco. The samples of water were collected from 20 wells in June 2017. We observed excessive concentrations of many parameters i.a.: NO3, Cd, Ni, Na, NH4, Cl, SO4, Fe, Cr. To determine the possibility to use the water for irrigation purposes, the Sodium Adsorption Ratio (SAR), sodium percentage (%Na), permeability index (PI), Kelly’s ratio (KR), magnesium hazards (MH) and electrical conductivity (EC) were assessed. The values of KR and MH qualified the waters as unsuitable for irrigation purposes. The observed %Na indicates that the groundwater is permissible for irrigation purposes, and permeability index, that it is of moderate quality. However, water classification using the SAR vs EC diagram confirms its high and very high alkali and salinity hazard. The mean EC value of the water was 9.5 mS cm−1.